Analysis of Mental Ray Rendering Techniques in 3D Animation Film Analisis Teknik Rendering Mental Ray Pada Film Animasi 3D - Bony Triwahyuda; Erwin Dwika Putra; Agung Kharisma Hidayah; Harry Witriyono (Penerbit Jurnal Indonesia, 2023)
Rendering is the final stage of the modeling or animation process. It is during this rendering that the polygons that make up a model will be computed on the computer to form an image. Along with the times, there are many rendering provider applications for 3D animation, one of which is Mental Ray. The formulation of the research problem is How long does it take to render a 3D animated film using mental ray and analyze the size of the rendered using mental ray? The development model in this study uses the Multimedia Development Life Cycle (MDLC) development which is the Luther version of the development method. Data collection by taking two finished or ready-to-rendering 3D films. The results show that the average length of time needed to render of The Little Human animation is 8.3 minutes, while the animated film Go Alex is 8.8 minutes. While the average size of the 12 rendered scenes of The Little Human animation is 17.3 mb and the animated film Go Alex is 17.8 Mb. Computer specifications will affect the performance of the rendering engine itself. This test only uses one type of computer, so to really test the performance of the rendering engine, a similar test is needed using several different types of computers and sepsis. When using the Autodesk Maya 2019 application, it is recommended to use incrementalSave to find out every step of the changes made, because it is to remember the steps to be taken if you forget and anticipate unexpected things such as blackouts.